Explanation:
for me it is best as a first step to combine this all to one big fraction, and then simplify the whole expression.
you do know that when multiplying the same variable with exponent we simply add the exponents. and she we divide the same variable with exponents, we subtract them from each other (as the overlapping exponent parts cancel each other out).
(3ac³f³)/(8a²bcf⁴) × (12ab²c)/(18ab³c²f) =
= (3×12a²b²c⁴f³)/(8×18a³b⁴c³f⁵) =
= (3×12c)/(8×18ab²f²) = 12c / (8×6ab²f²) =
= 2c / (8ab²f²) = c / (4ab²f²)